From Sargon To Narām-Sîn: some remarks on Akkadian military activity in the II nd half of the III rd millennium bc. The example of eastern campaigns - Paszke, Marcin Z. (Acta Archaeologica Lodziensia, 2022)
The present article discusses the phenomenon of Akkadian eastern military activity in the times of four consecutive Akkadian kings – Sargon, Rīmuš, Maništušu and Narām-Sîn. The author of the present investigation describes the course of Akkadian military expansion and attempts to characterize its cultural background by emphasizing that its economic and religious foundations constitute a part of the imperial strategy. It has been suggested that the religious ‒ and associated with it – the ideological factor, both embodied in the powerful image of the warlike goddess Aštar seem to be largely underestimated in the current academic discussion of the phenomenon of Akkadian expansion.